1995
DOI: 10.1002/sapm1995953319
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Stability and Turbulence: Beyond Transients to a Self‐Sustaining Process

Abstract: Transition from laminar to turbulent flows has generally been studied by considering the linear and weakly nonlinear evolution of small disturbances to the laminar flow. That approach has been fruitless for many shear flows, and a last hope for its success has been the existence of transient growth phenomena. The physical origin of those linear transient effects is elucidated, revealing serious limitations both of previous analyses and of the phenomena themselves, which preclude them from causing direct transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 39 publications
9
169
1
Order By: Relevance
“…Further inspection of the dynamics of each of the attached eddies revealed that the streaks and quasi-streamwise vortical structures form a self-sustaining process [41,55,65] exactly the same as the one shown in figure 3 with a turn-over time scale of Tu τ /λ z 2 [54]. The streaks are amplified from quasi-streamwise vortices via a coherent lift-up effect [26,30,35]; they then undergo rapid oscillation via secondary instability and/or transient growth on top of the streaks [39,40,42,55]; the quasi-streamwise vortical structures are nonlinearly regenerated [41,54,55]. The time scale of the self-sustaining process corresponds well to that of the 'bursting' in the logarithmic region, indicating that the bursting is naturally embedded in the self-sustaining process [54].…”
Section: Relation To Townsend's Attached Eddiesmentioning
confidence: 76%
See 2 more Smart Citations
“…Further inspection of the dynamics of each of the attached eddies revealed that the streaks and quasi-streamwise vortical structures form a self-sustaining process [41,55,65] exactly the same as the one shown in figure 3 with a turn-over time scale of Tu τ /λ z 2 [54]. The streaks are amplified from quasi-streamwise vortices via a coherent lift-up effect [26,30,35]; they then undergo rapid oscillation via secondary instability and/or transient growth on top of the streaks [39,40,42,55]; the quasi-streamwise vortical structures are nonlinearly regenerated [41,54,55]. The time scale of the self-sustaining process corresponds well to that of the 'bursting' in the logarithmic region, indicating that the bursting is naturally embedded in the self-sustaining process [54].…”
Section: Relation To Townsend's Attached Eddiesmentioning
confidence: 76%
“…In addition to the existence of the robust coherent lift-up effect discussed in §2, it was also shown that large-scale coherent streaks can undergo secondary instabilities at sufficiently large amplitudes [39,40], suggesting that a 'coherent' self-sustaining process similar to the buffer-layer one [41,42] might be at work also at larger scales in turbulent flows. To prove that such a type of process actually exists, however, it should be verified that motions of a given scale of interest are not sustained by larger-or smaller-scale motions.…”
Section: Self-sustaining Process At Large Scalementioning
confidence: 87%
See 1 more Smart Citation
“…The kinetic energy is splitted into its three components (E u , E v and E w ) additional phenomenon of internal gravity waves, it is possible that new forms of ECS could exist strictly for Ri b > 0. These would have different underpinning dynamics to that in unstratified flows (known variously as the self-sustaining process (SSP) - Waleffe (1995Waleffe ( , 1997 or Vortex-Wave-Interaction (VWI) -Hall & Smith (1991); Hall & Sherwin (2010)) and therefore would be of considerable interest. The investigation was started by reproducing Schneider et al's (2008) unstratified edge state calculation for (Re, Ri b , L x , L z ) = (400, 0, 4π, 2π).…”
Section: Identifying Ecs: Edge Trackingmentioning
confidence: 99%
“…For channel flows, Waleffe and co-workers, guided by the early ideas of Benney and colleagues, looked into the possibility that the Navier-Stokes equations might support wave systems occurring as instabilities of streamwise vortex flows but sufficiently large to drive the vortex flows; see for example Waleffe (1995Waleffe ( , 1997Waleffe ( , 1998Waleffe ( , 2001Waleffe ( , 2003, Wang et al (2007). The approach used was to find fully nonlinear solutions of the Navier-Stokes equations using various fictitious forces to identify equilibrium states and then continue them when the forcing was switched off.…”
Section: Introductionmentioning
confidence: 99%